Islam’s Marriage with Neoliberalism - Atasoy, Y. author. aut Link
VIII, 288 p.
Keywords: The transformation of the Turkish state is examined here in the context of globalized frames of neo-liberal capitalism and contemporary schemas of Islamic politics. It shows how the historical emergence of two distinct yet intertwined imaginaries of state structuring, laiklik and Islam, continues to influence Turkish politics today.